Evolving Historiographies: Strategies of Digital Platforms in Communicating Islamic History - Hannan, Haukil (UIN Sunan Ampel Surabaya, 2024)
This study explores the distinctions in historical narrative presentation between online platforms and traditional media, focusing specifically on how Islamic history is communicated across various digital outlets. Addressing two pivotal questions, the research first examines how the writing of history on online platforms diverges from conventional media forms. It then investigates the specific strategies employed by these digital platforms—Islamramah.co, Islami.co, Geotimes.id, and Muslim.or.id—to convey Islamic historical narratives to the public. Utilizing content analysis, the study evaluates narrative techniques, visual representations, and interactive elements that digital media integrate to enhance accessibility and engagement. The findings reveal that online platforms offer real-time dissemination, greater global reach, and multimodal content formats, which significantly alter public interaction with historical content. However, these advantages come with challenges, such as the potential for narrative fragmentation, algorithmic influence, and a tendency towards sensationalism. The study concludes that while online platforms facilitate broader access to historical narratives and foster public engagement, they also present risks that can compromise historical accuracy and depth. Thus, the research underscores the need for a balanced approach in digital historical communication.